Detecção e conscientização de portadores de hemoglobinopatias nas regiões de São José do Rio Preto e Presidente Prudente, SP (Brasil) - Naoum, Paulo César [UNESP]; Angulo, Ivan de Lucena; Brandão, Antônio Carlos; Graciano, Rejane Alexandre Silva; Spir, Marlene; Nomura, Eunice; Anjos, Irecê Deus (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1985)
Foram analisadas 7.657 amostras de sangue provenientes de 48 cidades das regiões de São José do Rio Preto e de Presidente Prudente, com o objetivo de detectar e conscientizar os portadores de hemoglobinas anormais. As análises efetuadas mostraram que 3,47% tinham hemoglobinas anormais, sendo 2,26% portadores de variantes moleculares (Hbs, AS, AC, SS, SC, AJ, AB2) e 1,21% de talasse-mias (alfa e beta). Os resultados obtidos evidenciaram que estudos semelhantes, além de propiciar o melhor conhecimento das causas genéticas, bioquímicas e hematológicas dessas alterações hereditárias, oferecem também a oportunidade de estimar a importância que essas patologias representam para a saúde pública do nosso país. A ação preventiva foi estabelecida por meio de reuniões de esclarecimentos médicos e biológicos aos portadores de hemoglobinas anormais.

A study of abnormal haemoglobins among the inhabitants of S. José do Rio Preto and Presidente Prudente was conducted, using blood samples collected from 7,657 subjects attending health clinics in 48 towns of those regions during 1983-1984. For purposes of analysis the subjects were grouped by region of origin and racial features, 6,941 being classified as caucasoid and 716 as negroid, the latter category including negroes, dark mulattoes, and light mulattoes. Electrophoretic techniques were used to detect abnormal haemoglobins, to determine the presence of haemoglobin types S and C, and isolate the polypeptide chains of other abnormal haemoglobins. Tests for quantification of haemoglobin A2 and fetal haemoglobin were performed as needed. Alpha and beta thalassaemias were diagnosed in accordance with principles established by the World Health Organization. These procedures detected abnormal haemoglobin in 266 (3.47%) of the study subjects. These included 173 specific molecular variants (169 of them being type S or type C variants) and 93 thalassaemias (4 of them being alpha thalassaemia and 89 beta thalassaemia, both in heterozygous state). Overall, the prevalence of abnormal haemoglobins was found to be higher among negroids (7.68%) than among the caucasoids (3.02%), and this difference was statistically significant (x²1; 0.01 = 6.64 x²1; 0.05 = 3.84). While the overall prevalence of abnormal haemoglobins among the S. José do Rio Preto subjects did not differ from prevalence among Presidente Prudente subjects, the prevalence of the genotypes detected among the populations analysed of these two cities, and their respective regions, was different. For S. José do Rio Preto and region, the Hb AS was more prevalent among the abnormal haemoglobins (63%), next came heterozygous beta thalassaemia (17%). For Presidente Prudente the prevalences of Hb AS and heterozygous beta thalassaemia, among the abnormal haemoglobins, were 46% and 40%, respectively. The preventive action to be taken was established by means of meetings at which medical and biological explanations were given to the carriers of abnormal haemoglobins. Overall, the results showed that similar studies offer better knowledge of genetic, biochemical and haemotological causes of these hereditary anaemias, and also provide the opportunity of discovering the importance that these pathological states have in the public health of the Brazilian population.
Detection of carriers of abnormal haemoglobins, and their familiarization with their condition, in the population of the regions of S. José do Rio Preto and Presidente Prudente, S. Paulo (Brazil)
Keywords: Hemoglobinas anormais; Talassemia; Anemia falciforme; Hemoglobinas anormais; Haemoglobins, abnormal; Thalassemia; Anaemia, sickle cell; Haemoglobins